Legal Strength Of Grant Deed Made By Land Deed Official In The Authenticity Of The Deed Perspective - Rahmawati, Aulia; Purba, Marlina br (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2024)
The position and strength of a PPAT deed as an authentic deed in the evidence system due to the lack of synchronization of laws and regulations, so it is interesting to conduct further research. One of the authentic deeds made by PPAT discussed in this thesis is a deed of gift, where to make a gift for immovable property can be done with an authentic deed or a deed under hand. However, to ensure legal certainty and to be a valid evidence, the transfer of the gift is carried out by making an authentic deed. The research uses the Normative Juridical method (legal research), namely legal research using legal norms as the object of its research based on an internal perspective that is able to provide legal arguments when conflicts, ambiguities, or legal gaps are found. The result is The power of grant deed made by the PPAT is a private deed, because the form and format of the deed of grant made by the PPAT are not regulated in the Law but are only regulated in the Ministerial Regulation. Therefore, the deed of grant made by the PPAT is not an authentic deed, so that its legal force remains binding on both parties but only as a private deed. The legal consequence of the deed of grant made by the PPAT is that the deed of grant is downgraded to a private deed because the position of the deed of grant made by the PPAT does not meet the qualifications of an authentic deed as stipulated in Article 1868 of the Civil Code. This is certainly detrimental to the parties, because the implementation of the grant as stipulated in Article 1682 of the Civil Code must be carried out with an authentic deed.